Macroeconomic Policy and Development in India: Some Analytical Issues - Partha Sen (Center for Economic Studies and ifo Institute (CESifo), 2022)
Should a developing economy, such as India, have a macroeconomic policy framework that is identical to an advanced capitalist country? The answer is a "No", because the developing economies have external constraints, that the more developed countries do not. They also, often, need to achieve a structural transformation by moving labour away from agriculture. These economies are, in addition, faced with possibility of international capital flow reversals. I argue for keeping the real exchange depreciated to have an export-led growth, emulating the East Asian experience. In today's world, given protectionism in the advanced capitalist countries, this strategy is more challenging. Also the capacity of the State to deliver this is open to question.
Keywords: E60; O10; O40; 330; inflation targeting; big push; exchange rates; structural transformation